AKUNTABILITAS PENGELOLAAN KEUANGAN DESA - Wiguna, Kusnadi Yudha; Dwilingga, Elia (Balance : Jurnal Akuntansi dan Bisnis, 2020)
The purpose of this research is to find out how the accountability of village financial management in Megang Sakti V Village Megang Sakti District Musi Rawas District. This type of research is descriptive research with qualitative data analysis using primary and secondary data sources. Primary data sources, namely through observation and interviews. The secondary data source is through regulations related to village financial management in 2018. The results showed that there was a delay in accountability at the implementation stage in submitting a payment request which led to delays in the administration, reporting and accountability stages. At the administration stage there is also a delay, apart from being due to the delay in this implementation stage, also due to the limited ability and knowledge of village apparatus resources in running village financial system applications which have an impact on delays in the next stage, namely reporting and accountability.